Properties of metakaolin-blended oil palm shell lightweight concrete - Mo, Kim Hung; Mohd Anor, Fatin Amirah; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Rao, K. Jagannadha (Taylor & Francis, 2018)
In this paper, the effect of partial replacement of cement with metakaolin (MK) on the strength properties of oil palm shell (OPS) lightweight concrete was investigated. Generally, 5–20% of partial cement replacement with MK enhanced the compressive, splitting tensile and flexural strengths as well as modulus of elasticity of OPS concrete (OPSC). Though the 28 day compressive strength of the OPSC was found in the range of 39–47 MPa, the highest compressive strength was obtained for the mix with 10% replacement of MK. Similar replacement level of MK was found optimum for both the splitting tensile and flexural strengths. In addition, the strength efficiency of OPSC with MK as partial cement replacement was also investigated and it was found that the increase in the replacement level of MK up to 20% resulted in 49% increase in the strength efficiency for the OPSC.